PENGARUH RELEVANSI KURIKULUM, PERILAKU BELAJAR, DAN KETAHANMALANGAN TERHADAP KOMPETENSI LULUSAN PESERTA PROGRAM MAGANG PADA PT. CHEVRON PACIFIC INDONESIA - Hutahaean, Thomas (JERAM, 2017)
ABSTRACT   The purpose of this research is to determine the factors that affect the competence of the participants graduate internship program (called it COOPs = Cooperative students) at PT Chevron Pacific Indonesia. This type of research is quantitative associative by using path analysis. Sampling technique research using simple random sampling technique, while the data collection techniques using questionnaires. Based on the research, the following results are obtained: (1) there is a direct positive effect of curriculum relevance to the competence of graduates, (2) there is a direct positive effect of learning behavior toward the competence of graduates; (3) there is direct positive effect of curriculum relevance to adversity quotient; (5) there is a direct positive effect of curriculum relevance to learning behavior, and (6) there is a positive direct effect of adversity quotient to the competence of graduates of apprenticeship program participants of PT. Chevron Pacific Indonesia.